2019
DOI: 10.1061/(asce)gm.1943-5622.0001463
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Drying-Wetting and Loading-Unloading Cycles on Small Strain Shear Modulus of Unsaturated Soils

Abstract: The small strain shear modulus (G max) is an important parameter in geodynamic problems. In order to predict G max of unsaturated soils which are normally subjected to complex drying, wetting processes, effect of hydraulic hysteresis needs to be evaluated. Although several equations have been proposed in recent years, limitations still exist, requiring more research studies in this field. In this study, G max was investigated in a multi-stage test during several drying-wetting cycles and a loading-unloading cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 71 publications
2
12
1
Order By: Relevance
“…Nevertheless, Anggraini et al (2016) indicated that wetting-drying cycles could make the curing time longer, and therefore the durability of stabilized soils was enhanced. Similar strengthening behaviour was observed on untreated soil -Gmax increased with increasing wetting-drying cycles due to the effect of suction history-related decrease of saturation degree and void ratio (Heitor et al, 2015;Ngoc et al, 2019;Khosravi et al, 2020). Estabragh et al (2013) investigated the wetting fluid (distilled water, saline water and acidic water) effect on the volume change of swelling soil during wetting-drying cycles.…”
Section: Introductionsupporting
confidence: 53%
“…Nevertheless, Anggraini et al (2016) indicated that wetting-drying cycles could make the curing time longer, and therefore the durability of stabilized soils was enhanced. Similar strengthening behaviour was observed on untreated soil -Gmax increased with increasing wetting-drying cycles due to the effect of suction history-related decrease of saturation degree and void ratio (Heitor et al, 2015;Ngoc et al, 2019;Khosravi et al, 2020). Estabragh et al (2013) investigated the wetting fluid (distilled water, saline water and acidic water) effect on the volume change of swelling soil during wetting-drying cycles.…”
Section: Introductionsupporting
confidence: 53%
“…In the literature, similar observation was reported. The observed increase in G max may be attributed to the plastic hardening as soil dries and develops suction [1,16]. Fig.…”
Section: Test Programmentioning
confidence: 88%
“…Shear moduli at very small strain (G max ) and large strains (G), are crucial parameters for predicting soil movements and response of soil-structure system when subjected to dynamic loading and when investigating the quality of earthworks via a spectral analysis of surface waves [1]. The constraint modulus (M), on the other hand, was another important soil parameter when designing buried pipe lines and pavements [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…During the drying process, the water content decreases and the air content increases, resulting in an increase in the van der Waals attraction and reduction of the electrical double repulsion. This results in the aggregation of clay particles [35]. On the contrary, during the wetting process, soil suction and van der Waals attraction between soil particles will decrease, and the electrical double layer repulsion will increase.…”
Section: Structure Of Expansive Soilsmentioning
confidence: 99%